2010
DOI: 10.1007/s11104-010-0687-5
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus in pasture plants: potential implications for phosphorus loss in surface runoff

Abstract: Phosphorus (P) loss from land can impair surface water quality. Losses can occur from soil and plant components. While it is known that P losses increase with soil P concentration, it is not known how losses from pasture plants vary with soil P concentration or between different forages. We examined total P and filterable reactive P (FRP) in water extracts of plant shoots, used as a measure of potential P loss to surface runoff, in different forage species relative to soil P concentration in field trials and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…This indicates that selective breeding for levels of micro-and macro-minerals is feasible and that genomic selection represents a strong option for pursuing improvement in these traits. In general, ryegrass cultivars that grow well under low soil P will compete less for P in the sward, increasing P availability for uptake to support legume growth (Easton et al 1997;McDowell et al 2011). For instance, Crush et al (2006), reported that in a mixed sward of ryegrass and clover (18% clover content), net annual flux of P into ryegrass was 4.7 times higher compared to clover.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that selective breeding for levels of micro-and macro-minerals is feasible and that genomic selection represents a strong option for pursuing improvement in these traits. In general, ryegrass cultivars that grow well under low soil P will compete less for P in the sward, increasing P availability for uptake to support legume growth (Easton et al 1997;McDowell et al 2011). For instance, Crush et al (2006), reported that in a mixed sward of ryegrass and clover (18% clover content), net annual flux of P into ryegrass was 4.7 times higher compared to clover.…”
Section: Discussionmentioning
confidence: 99%
“…Following this the loam soil with native M3P concentration 20 mg/kg (labeled M3P20 hereafter) was spiked with different concentrations of superphosphate (9 g/kg total phosphorus (TP)) fertilizer. Fertilizer was added to increase M3P concentrations to 23, 30, 44, 62, 97, 187, 428, and 679 mg/kg (after McDowell et al ., ). It was then incubated for 168 days with periodic soil wetting to maintain an approximate soil moisture content of 30% by weight approximately equivalent to saturated field moisture.…”
Section: Methodsmentioning
confidence: 97%
“…Selection of more P-efficient pasture cultivars is one possible change. Species and cultivars may differ greatly in shoot P concentrations at a given level of extractable soil P, and in external critical P requirements, with grasses generally presenting lower shoot P concentrations and a lower external critical P requirement than legumes (Ozanne et al 1969;McDowell et al 2011;Sandral et al 2015;Haling et al 2016). Thus, decreasing the rate of P-fertiliser addition to pastures to match the P requirements of grasses only, or of annual legumes with lower P requirements than the current widely-used species T. subterraneum, would reduce the size of the pool of readily-soluble P circulating through plants and top soil layers and thus reduce the risk of losses.…”
Section: How Can Stratification Be Reduced?mentioning
confidence: 99%